2014
DOI: 10.1007/s11695-014-1460-2
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Bariatric Surgery for Type 2 Diabetes: Systematic Review and Meta-analysis of Randomized and Non-randomized Evidence

Abstract: This study aims to assess the long-term effects of bariatric surgery on type 2 diabetic patients. We searched Cochrane Library, PubMed, and EMbase up to Dec 2013. Randomized controlled trials (RCTs) and cohort studies of bariatric surgery for diabetes patients that reported data with more than 2 years of follow-up were included. We used rigorous methods to screen studies for eligibility and collected data using standardized forms. Where applicable, we pooled data by meta-analyses. Twenty-six studies, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(75 citation statements)
references
References 45 publications
4
68
0
3
Order By: Relevance
“…10 A more recent study that assessed the long-term effects of bariatric surgery on diabetic patients observed that glucose control and remission from diabetes were possible in 89.2% and 64.7% of the patients, respectively. 30 Similar findings had already been reported previously. 31 Furthermore, reduction of diabetes has been found to occur more frequently among patients who underwent gastric bypass surgery that excluded the duodenum from the nutrient pathway and changed the bowel metabolism, thus reducing insulin resistance faster.…”
Section: Antidiabetic Drugssupporting
confidence: 87%
“…10 A more recent study that assessed the long-term effects of bariatric surgery on diabetic patients observed that glucose control and remission from diabetes were possible in 89.2% and 64.7% of the patients, respectively. 30 Similar findings had already been reported previously. 31 Furthermore, reduction of diabetes has been found to occur more frequently among patients who underwent gastric bypass surgery that excluded the duodenum from the nutrient pathway and changed the bowel metabolism, thus reducing insulin resistance faster.…”
Section: Antidiabetic Drugssupporting
confidence: 87%
“…Close follow-up of 88 patients revealed a satisfactory result in weight loss. Recent large meta-analyses and reviews have shown that weight loss and diabetes remission are greatest and last longer in patients undergoing biliopancreatic diversion and gastric bypass [28]. But sleeve gastrectomy also provides satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest amount and durability of weight lost as well as degree of remission of diabetes occur with the (infrequently used) biliopancreatic diversion with duodenal switch followed, in order, by the Roux-en-Y gastric bypass, sleeve gastrectomy, and gastric banding (22). One finding common to all bariatric surgeries is that, over time and on average, patients regain some of the weight that they initially lost.…”
Section: Comparative Effect Of Bariatric Surgery On Weight and Remissmentioning
confidence: 99%